Perception of Undergraduate Medical and Health Sciences Students Regarding Online Formative Assessments During COVID-19 - Ain, Noor Ul; Jan, Sadiq; Yasmeen, Rahila; Mumtaz, Hassan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look into the experience of undergraduate medical and health sciences students regarding perceptions of online formative assessments. Study Design: Online cross-sectional survey. Place and Duration of Study: Riphah International University, Islamabad Pakistan, from Aug to Dec 2020. Methodology: Three hundred fifty-one pre-clinical and clinical students of disciplines including MBBS, BDS, and Pharm-D participated in the study. Data was collected through a convenient sampling technique. An online questionnaire containing 22 closed-ended questions with a three-point Likert scale on five themes related to online formative assessments and one openended question was used. Results: 86 (24.5%) students agreed that online formative assessments improved their learning. The motivation for learning was increased in 120 (34.2%) students. 214 (61%) students felt that online formative assessments were stressful, and the majority were well aware of the use of technology except for connectivity and login issues highlighted by the students. Regarding the question paper, the majority were comfortable with the construct of online formatives. 158 (45%) students were not satisfied with the allotted time to complete the formative assessments. 163 (46.4%) students were satisfied with the feedback provided, yet 258 (73.5%) students recommended formal feedback provided on the same day to improve their learning by knowing their deficiencies. Conclusion: The study results support the contention that well-designed online formative assessments have considerable untapped potential to assist learning by motivating students. Their problems and challenges need to be addressed to improve the online assessments that help in the learning of undergraduate students.